1987
DOI: 10.1164/ajrccm/136.2.369
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Histamine to Immediate Bronchoconstriction Provoked by Inhaled Allergen and Adenosine 5′ Monophosphate in Atopic Asthma

Abstract: In order to investigate the contribution of histamine to bronchoconstriction provoked by inhaled allergen and adenosine monophosphate (AMP), we have observed the effects of prior treatment with the potent H1-receptor antagonists, terfenadine and astemizole. Nine mild, atopic asthmatics underwent inhalation challenge tests on 6 separate days with histamine, allergen extract, and AMP using single concentrations previously shown to produce a 30% fall in FEV1. For each agonist, bronchoprovocation was performed 3 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
82
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(86 citation statements)
references
References 7 publications
4
82
0
Order By: Relevance
“…35 Binks et al showed that chest tightness may occur in association with bronchoconstriction, in subjects ventilated passively on a mechanical ventilator and that production of an elevated FRC with ventilator generated positive end expiratory pressure did not result in chest tightness. 36 Furthermore, Taguchi et al suggested that dyspnea sensation may result from stimulation of airway receptors when they observed a reduced sensation of dyspnea during histamine-induced bronchoconstriction under airway anesthesia by lidocaine aerosol inhalation. 37 We observed a correlation between maximum decreases in FEV1 and IC following MC, but again, breathlessness scores were not correlated with the decrease in IC.…”
Section: Discussionmentioning
confidence: 99%
“…35 Binks et al showed that chest tightness may occur in association with bronchoconstriction, in subjects ventilated passively on a mechanical ventilator and that production of an elevated FRC with ventilator generated positive end expiratory pressure did not result in chest tightness. 36 Furthermore, Taguchi et al suggested that dyspnea sensation may result from stimulation of airway receptors when they observed a reduced sensation of dyspnea during histamine-induced bronchoconstriction under airway anesthesia by lidocaine aerosol inhalation. 37 We observed a correlation between maximum decreases in FEV1 and IC following MC, but again, breathlessness scores were not correlated with the decrease in IC.…”
Section: Discussionmentioning
confidence: 99%
“…Adenosine has been implicated to contribute to the pathophysiology of asthma as inhaled adenosine provokes bronchoconstriction in asthmatic but not normal patients (38). The response to adenosine is believed to be predominantly mediated through mast cell activation (39). Attempts to elucidate definitively the adenosine receptor subtype that mediates mast cell activation has been pharmacologically difficult due to lack of agonists and antagonists that display sufficient selectivity to discriminate between multiple adenosine receptor subtypes present on these cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, RS-601 did not affect the antigen-induced IAR in this model. Rafferty et al [29] reported that histamine participated in IAR observed in atopic asthmatic patients. In our model, histamine was markedly increased in BALF, corresponding to the appearance of IAR [30], and the IAR was clearly inhibited by the histamine H 1 receptor antagonist terfenadine [31].…”
Section: Discussionmentioning
confidence: 99%